(untitled) (Journal of the College of Basic Education, 2025)
Britain played a pivotal role in reshaping the judicial system in Iraq during the British occupation following the fall of the Ottoman Empire in the early twentieth century. After the occupation of Baghdad in 1917, the British authorities began laying new foundations for the organization of the judiciary, aiming to replace the existing Ottoman system with one more compatible with their political and administrative interests.